2001
DOI: 10.1007/s007740170026
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblot detection and expression of enamel proteins at the apical portion of the forming root in porcine permanent incisor tooth germs

Abstract: There have been many immunohistochemical studies of enamel proteins during root formation. In the present article, the detection and expression of enamel proteins in tissue samples prepared from the apical portion of the forming root (APFR) in porcine permanent incisor tooth germs were studied. Amelogenin, enamelin, and sheathlin were detected by immunoblot analysis, but only in small amounts. The detection of their derivatives indicated their degradation. It is, at present, unclear as to which proteinases are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…During tooth development, at least nine different mRNA splice forms are generated from the amelogenin gene as a result of alternate splicing (26). Interestingly, the presence of amelogenins in the tooth root region has been detected only by immunohistochemical and in situ hybridization studies (9,10,27). However, these studies could not identify the presence of individual alternate splice forms of mRNA or their translational products.…”
Section: Figmentioning
confidence: 58%
“…During tooth development, at least nine different mRNA splice forms are generated from the amelogenin gene as a result of alternate splicing (26). Interestingly, the presence of amelogenins in the tooth root region has been detected only by immunohistochemical and in situ hybridization studies (9,10,27). However, these studies could not identify the presence of individual alternate splice forms of mRNA or their translational products.…”
Section: Figmentioning
confidence: 58%
“…12,13 In fact, EMPs have been recently detected at the apical portion of the forming root by immunoblot analysis. 14 The introduction of EMD in periodontal regeneration was based on the apparent involvement of EMPs in the formation of acellular cementum and associated tooth-supporting tissues during root morphogenesis. [9][10][11][12][13][14] It was hypothesized that surgical application of EMD on previously diseased roots may form a natural extracellular matrix that controls regenerative processes, mimicking developmental interactions in a clinical setting.…”
Section: The Biological Principle Of Emd Guided Regeneration (Egr)mentioning
confidence: 99%
“…14 The introduction of EMD in periodontal regeneration was based on the apparent involvement of EMPs in the formation of acellular cementum and associated tooth-supporting tissues during root morphogenesis. [9][10][11][12][13][14] It was hypothesized that surgical application of EMD on previously diseased roots may form a natural extracellular matrix that controls regenerative processes, mimicking developmental interactions in a clinical setting. 7,15 In support of this hypothesis, it has been demonstrated that EMD precipitated on root surfaces forms aggregated microspheres 7,16 that resemble the in vivo supramolecular globular assemblies of the EM.…”
Section: The Biological Principle Of Emd Guided Regeneration (Egr)mentioning
confidence: 99%
“…In particular, amelogenins are believed to initiate specifically the genesis of acellular extrinsic fiber cementum (Hammarström 1997, Hammarström et al 1997). While experimental data confirming this assumption are lacking, several studies used biochemical (Slavkin et al 1989a, b, Fukae et al 2001) and histological (Slavkin et al 1989b, Luo et al 1991, Bosshardt & Schroeder 1996, Fong et al 1996, Thomas et al 1997, Bosshardt & Nanci 1998, 2000, Fong & Hammarström 2000, Hu et al 2001) techniques to demonstrate protein and gene expression of EMPs during root development. Slavkin et al (1989b) demonstrated both amelogenin and enamelin protein expression along the cervical‐most portion of growing molars from young mice, a region where acellular extrinsic fiber cementum prevails.…”
mentioning
confidence: 99%